Reforma al título iv de los riesgos del trabajo. Para el art. 356, con lo referente a los trabajadores no suscritos al régimen del seguro social obligatorio de riesgo - Ugarte Ramos, William Moisés (2015)
Our Constitution in the eighth section letter speaks of labor and social security, Article 33 says that the work is an inalienable right and also an economic right, a source of personal fulfillment and the basis of the country's economy. As the right to work mentioned is a social duty, Social Security is an inalienable right of all the people and also as a primary duty of the state, which will be governed by the principles of solidarity, obligation, universality, equity, efficiency, subsidiarity , adequacy, transparency and participation to meet the people who need this service because the state will implement the full implementation of this right in all forms of work. The constitution states that Social Security is an inalienable right of all the inhabitants of Ecuador and a state duty; for it has been established that whoever preset service whether physical or intellectual to another person, that is for an employer, this has the obligation to provide social security to which they are entitled. In our country Ei mandatory universal insurance will cover the contingencies of sickness, maternity, paternity, workplace hazards, unemployment, unemployment, old age, disability, disability, death and those defined by the law. Health benefits of the contingencies of sickness and maternity will be provided through the comprehensive public health network. But although the Constitution of Ecuador, the international treaties and the law of social security mentioned on social security and guarantees to people who work under the dependency ratio this right still looks I violated Article Art. 356 of the Code Working in giving the authority to the employer of hiring a medical insurance if you go without compulsory social insurance Risk-law must be that every employer has the compulsory insurance for these reasons has been made legal, social study analyze this issue of vital importance